Design and test of the arc-shaped nail-tooth roller residual film recovery machine from the sowing layer - Zhang, Zhiyuan; Chen, Xuegeng; Wang, Xianfei; Xue, Shuaikang; Li, Jingbin (International Journal of Agricultural and Biological Engineering, 2024)
Residual films on the sowing layer produced after mulching in Xinjiang farmland, harm the sowing quality and root growth of crops. In this study, a sowing layer residual film recovery machine based on a radial plate arc-shaped nail-tooth roller structure was designed. Meanwhile, the key device structures were designed and the main working parameters were analyzed. Then, taking the working depth, the forward speed of the machine and the rotation speed of the nail tooth roller as the test factors, and the film collection rate and film intertwining rate as the test indicators, the single factor tests and the Box-Behnken response surface tests were carried out to evaluate the performance of the sowing layer residual film recovery machine. Consequently, the results showed that the order of significant factors was the working depth, the forward speed of the machine, and the rotation speed of the nail tooth roller. Besides, the optimal working parameters were determined, which the working depth, the forward speed of the machine, and the rotation speed of the nail tooth roller were 100 mm, 4.8 km/h, and 49.3 r/min, respectively. Moreover, the predicted value of the film collection rate was 69.20%. Finally, the verification test was taken with the optimal working parameter, and the results showed that the film collection rate was 66.84%, and the film intertwining rate was 1.39%. The relative error between the test value and the predicted value of the film collection rate was 3.40%. It indicated that the machine can perform the collection of sowing layer residual films. This study can provide a theoretical basis and reference for the design of new sowing layer residual film machines. Keywords: residual film recycling machine, mulching film, pick-up device, seedbed preparation DOI: 10.25165/j.ijabe.20241701.6993 Citation: Zhang Z Y, Chen X G, Wang X F, Xue S K, Li J B. Design and test of the arc-shaped nail-tooth roller residual film recovery machine from the sowing layer. Int J Agric & Biol Eng, 2024; 17(1): 90-98.